MODEL ESTIMASI TERINTEGRASI BIAYA LANGSUNG PELAKSANAAN KONSTRUKSI DENGAN JADWAL PELAKSANAAN - Adnyana Putera, I Gusti Agung (Jurnal Ilmiah Teknik Sipil, 2009)
Estimation of duration and cost of a project are two classical problems that always arise in the real world construction project. In the current practice, the cost is analyzed separately from a planning by estimators. In fact, time and cost of the construction project depend on what kind of product to be constructed, how to realize it, when and where it has to be constructed. They have an intimate interrelationship and can not be separated while analyzing them. When a planning of activities is changed, the project cost would change as well. The existing cost model does not integrate this relation. The project cost is estimated based on the assumed rates of construction resources and gross quantity of works without taking into account how the activities will be performed. This paper proposes a cost model that can integrate the planning and the construction direct cost based on the daily necessary resources of the related planning. It presents also some examples of its application. This model is very useful to simulate the real project direct cost from an estimated planning before executing the project. The accuracy of the result depends completely on the accuracy of estimated planning and the basic information corresponding to time and cost estimation of an elementary activity.
Keywords: Construction direct cost, planning, estimation, cost model.